2019
DOI: 10.1038/s41467-019-09400-w
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium disulfide flakes with nanolayered titanium disulfide coating as cathode materials in lithium-ion batteries

Abstract: Unlike the vast majority of transition metal dichalcogenides which are semiconductors, vanadium disulfide is metallic and conductive. This makes it particularly promising as an electrode material in lithium-ion batteries. However, vanadium disulfide exhibits poor stability due to large Peierls distortion during cycling. Here we report that vanadium disulfide flakes can be rendered stable in the electrochemical environment of a lithium-ion battery by conformally coating them with a ~2.5 nm thick titanium disulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 49 publications
(51 reference statements)
1
56
0
Order By: Relevance
“…In situ TEM has been widely applied to reveal the underlying mechanisms of rechargeable batteries, including LIBs, Li–O 2 batteries, Li–S batteries, lithium metal batteries, sodium‐ion batteries, sodium–O 2 batteries, and Li–Se batteries …”
Section: Energy Storagementioning
confidence: 99%
“…In situ TEM has been widely applied to reveal the underlying mechanisms of rechargeable batteries, including LIBs, Li–O 2 batteries, Li–S batteries, lithium metal batteries, sodium‐ion batteries, sodium–O 2 batteries, and Li–Se batteries …”
Section: Energy Storagementioning
confidence: 99%
“…Using the first-principles density functional theory calculations, Wang et al reported that a monolayer VS 2 can absorb three layers of Li-ion, producing a high theoretical capacity of 1397 mAh g −1 [21] , which makes VS 2 a promising electrode material for LIBs. However, VS 2 -based electrodes suffer from low reversible capacity and poor cycling stability mainly related to the volume variations generated during the charge/discharge processes [22,23] . In order to buffer the volume variations for improving the stability, VS 2 is incorporated with mechanically resilient carbon materials or transition metals to form composites [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…However, VS 2 -based electrodes suffer from low reversible capacity and poor cycling stability mainly related to the volume variations generated during the charge/discharge processes [22,23] . In order to buffer the volume variations for improving the stability, VS 2 is incorporated with mechanically resilient carbon materials or transition metals to form composites [22][23][24] . For instance, Fang et al reported that VS 2 @graphene nanosheets could deliver a high reversible capacity of 528 mAh g −1 after 100 cycles at 200 mA g −1 [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern human society cannot flourish without an efficient, affordable and safe means for energy storage. Presently, Lithium (Li) -ion batteries (LIBs) are dominating the energy storage landscape from portable electronics and grid storage to the rapidly expanding electric vehicles market 1,2,3,4,56 . As the range of applications of LIBs expand, it is becoming increasingly clear that the traditional LIB chemistry (i.e., the graphite anode and transition metal oxide cathode) is not well-suited in many situations 7,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%